Food Prices and Population Health in Developing Countries: An Investigation of the Effects of the Food Crisis Using a Panel Analysis - Suejin Lee; Jae-Young Lim; Hyun-Hoon Lee; Cyn-Young Park (Asian Development Bank (ADB), 2013)
High food prices can be an immediate threat to household food security, undermining population health, retarding human development, and lowering labor productivity for the economy in the long term. We employ a panel dataset covering 63 developing countries from 2001 to 2010 to make a comprehensive assessment of the effects of food price inflation and volatility on population health measured by infant mortality rate, child mortality rate, and the prevalence of undernourishment. We find that rising food prices have a significant and adverse effect on all three health indicators in developing countries. Furthermore, the impact of food prices is severer in the least developing countries although the effect is moderated in countries with a greater share of agriculture in gross domestic product.
hdl:11540/2069
Keywords: I15; I18; I19; Q18; 330; food price; health; food security